2019
DOI: 10.1002/ehf2.12406
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HLA‐A, ‐B, ‐C, ‐DRB1 and ‐DQB1 allele and haplotype frequencies in heart failure patients

Abstract: Aims Cell therapy can be used to repair functionally impaired organs and tissues in humans. Although autologous cells have an immunological advantage, it is difficult to obtain high cell numbers for therapy. Well‐characterized banks of cells with human leukocyte antigens (HLA) that are representative of a given population are thus needed. The present study investigates the HLA allele and haplotype frequencies in a cohort of heart failure (HF) patients. Methods and results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The HLA haplotype landscape in Spain has been investigated before with small cohorts of patients and healthy individuals [ 21 23 ] and a larger cohort of 5458 units of cord blood from the Barcelona Cord Blood Bank, HLA-typed in high resolution [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The HLA haplotype landscape in Spain has been investigated before with small cohorts of patients and healthy individuals [ 21 23 ] and a larger cohort of 5458 units of cord blood from the Barcelona Cord Blood Bank, HLA-typed in high resolution [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…CD44 is also crucial in the development of cardiac remodelling and myocardial fibrosis, which accelerates the progression to heart failure 39 . In addition, HLA‐A and HLA‐B also play potential roles in heart failure 40 . These findings suggest that it is worth investigating the exact role of these hub genes in heart failure following HTx and whether the expression of these hub genes in different myocardial regions has different patterns to affect the development of heart failure following HTx.…”
Section: Discussionmentioning
confidence: 99%
“…Human-to-human transmission was reported only after the zoonotic transmission of the new virus via animals in the seafood market [1]. Finally, having a higher transmission rate than SARS-CoV and MERS-CoV, and the high affinity of the viral spike protein for its receptor angiotensin-converting enzyme 2 (ACE-2), WHO announced SARS-CoV-2 as a pandemic on 12 March 2020 [2,3]. Currently, SARS-CoV-2 has spread globally and led to all research focusing on improving methods of the diagnosis, treatment, prognosis, vaccine design, and control of COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%
“…HLA alleles are the most highly polymorphic genes, and the heterozygote advantage of HLA genotypes affects their ability to respond to different pathogens and even control or intensify an infectious disease [8,9]. The association of HLA alleles with some viral infections (such as HIV, HBV, H1N1, and HCV) and some chronic diseases is well established [7,[10][11][12][13]. Wang et al showed that HLA-Cw 15 : 02, DR 03 : 01 and HLA-B * 46 : 01, B * 07 : 03, DRB1 * 12 : 02 were associated with resistance and severity of SARS-CoV, respectively [14,15].…”
Section: Introductionmentioning
confidence: 99%